2017
DOI: 10.1002/aoc.4168
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization and immobilization of a novel mononuclear vanadium (V) complex on modified magnetic nanoparticles as catalyst for epoxidation of allyl alcohols

Abstract: The 2,4,6‐tris(2‐pyridyl)‐1,3,5‐triazine (tptz) undergoes hydrolysis in the presence of VO(SO4) in an alkaline solution, affording mainly the bis(2‐pyridyl carbonyl)amid) VO2 complex, designated as [VO2(bpca)]. Single‐crystal X‐ray crystallography revealed that the coordination of V in complex is a distorted square‐pyramid coordinated with three nitrogen of bis(2‐pyridyl carbonyl)amid) ligand and two binding oxygen atoms. The prepared complex which successfully supported on modified Fe3O4 nanoparticles using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 92 publications
2
8
0
Order By: Relevance
“…Finally, concomitant elimination of tert ‐butanol and epoxide regenerates the catalyst (Scheme ). Since the formation rate of III in the nucleophilic attack of double bond to the oxygen electrophile depends on the number of alkyl substitutions present on the double bonds, it can be concluded that the geraniol which contains a trisubstituted double bonds exhibit the highest epoxidation rate. On the other hand, trans ‐2‐ hexen‐1‐ol and 1‐octen‐3‐ol containing disubstituted and monosubstituted double bonds would undergo epoxidation reactions in lower rates, respectively.…”
Section: Resultssupporting
confidence: 55%
See 2 more Smart Citations
“…Finally, concomitant elimination of tert ‐butanol and epoxide regenerates the catalyst (Scheme ). Since the formation rate of III in the nucleophilic attack of double bond to the oxygen electrophile depends on the number of alkyl substitutions present on the double bonds, it can be concluded that the geraniol which contains a trisubstituted double bonds exhibit the highest epoxidation rate. On the other hand, trans ‐2‐ hexen‐1‐ol and 1‐octen‐3‐ol containing disubstituted and monosubstituted double bonds would undergo epoxidation reactions in lower rates, respectively.…”
Section: Resultssupporting
confidence: 55%
“…Finally, comparison of the epoxidation results of geraniol catalyzed by Fe 3 O 4 @SiO 2 @CPTMS@‐Mel‐Naph‐VOcomplex in this work with some previously reported heterogeneous catalysts provided in Table reveals that conversion, selectivity, TON and TOF of our catalysis system is considerable …”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…3032 The allyl alcohol epoxidation is a big challenge in the industrial point of view because of their wide range of applications in the field of organic synthesis and pharmaceuticals. 3338 Allyl alcohol undergoes epoxidation and gives glycidol. Glycidol is used as an oil additive, precursor, and stabilizer for the synthesis of novel polymers.…”
Section: Introductionmentioning
confidence: 99%
“…Fe 3 O 4 coated as a magnet core and supported by organic compounds has found a special place in the synthesis of heterogeneous magnetic nanocatalysts as such many relevant studies have been carried out in this regard . In addition, Fe 3 O 4 supported and coated can create complexes with different metals and synthesized magnetic organometallic nanocatalysts . A review of the literature also elaborates on the use of nickel metal in the synthesis of organic compounds .…”
Section: Introductionmentioning
confidence: 99%